Automatic Guidance (and Misguidance) of Visuospatial Attention by Acquired Scene Memory: Evidence From an N1pc Polarity Reversal. (December 2020) - Zinchenko, Artyom; Conci, Markus; Töllner, Thomas; Müller, Hermann J.; Geyer, Thomas
Visual search is facilitated when the target is repeatedly encountered at a fixed position within an invariant (vs. randomly variable) distractor layout—that is, when the layout is learned and guides attention to the target, a phenomenon known as contextual cuing . Subsequently changing the target location within a learned layout abolishes contextual cuing, which is difficult to relearn. Here, we used lateralized event-related electroencephalogram (EEG) potentials to explore memory-based attentional guidance ( N = 16). The results revealed reliable contextual cuing during initial learning and an associated EEG-amplitude increase for repeated layouts in attention-related components, starting with an early posterior negativity (N1pc, 80–180 ms). When the target was relocated to the opposite hemifield following learning, contextual cuing was effectively abolished, and the N1pc was reversed in polarity (indicative of persistent misguidance of attention to the original target location). Thus, once learned, repeated layouts trigger attentional-priority signals from memory that proactively interfere with contextual relearning after target relocation.